IMPLEMENTASI KEBIJAKAN RETRIBUSI PASAR DALAM MENUJANG PENDAPATAN ASLI DAERAH DI KABUPATEN HALMAHERA UTARA - Hohakay, Kristina; Rompas, Wilson; Rares, Joyce (Sam Ratulangi University, 2015)
ABSTRACT : Levies are a source of potential revenue because of the scope of the imposition of levies broaderin appeal with the local tax. Similarly, according to Adisasmita R (2011) that the development levies easier than theimposition of local taxes considering the scope of the levies are not as strict as compared to local taxes. Therefore, localgovernments in order to develop PAD more focused on increasing acceptance levies.This study uses qualitative descriptive method. The informants were 20 people who were taken from berbegaielements of government officials, workers and public collectors / traders market. The main instrument in this study isthe researchers themselves are, while collecting data using interview techniques and assisted with the observationdanstudi dokmentasi. Data analysis was performed using descriptive-qualitative analysis interactive model of Miles andHubernann.Results of the study provides conclusions: (1) Management Levy Markets in North Halmahera is theresponsibility and authority of the Office of Perindakop and SMEs, and fully implemented by the trade sector as anelement of the implementation of the coordination of activities of the Department of Perindakop and SMEs which carryout the collection of the levy markets and market management system uses official assessment is based on RegionalRegulation No. 5 of 2007, namely ballot directly to the voting system uses valuable objects in the form of a ticket.From the above conclusion, the writer can give suggestions as follows 1) To increase the successfulimplementation of market tax policy, the Department Perindakop and SMEs in North Halmahera District madeadditional levy collection officer existing markets in order to bias a balance between the amount of workload and HR2) To enhance the successful implementation of market tax policy, then pemrintah in this case the DepartmentPerindakop and SMEs as market tax policy implementers should review the market that is not active and make efforts toimprove the quality of the market in order to attract traders to use the market as a trade so biased levy optimize marketacceptance.Keywords: Retribution Policy Implementation Markets in Supporting Local Revenue.